Genetic and Biochemical Characterization of the Cell Wall Hydrolase Activity of the Major Secreted Protein of Lactobacillus rhamnosus GG - Claes, Ingmar J. J.; Schoofs, Geert; Regulski, Krzysztof; Courtin, Pascal; Chapot-Chartier, Marie-Pierre; Rolain, Thomas; Hols, Pascal; von Ossowski, Ingemar; Reunanen, Justus; de Vos, Willem M.; Palva, Airi; Vanderleyden, Jos; et al. (PLOS ONE, 2012)
Lactobacillus rhamnosus GG (LGG) produces two major secreted proteins, designated here Msp1 (LGG_00324 or p75) and Msp2 (LGG_00031 or p40), which have been reported to promote the survival and growth of intestinal epithelial cells. Intriguingly, although each of these proteins shares homology with cell wall hydrolases, a physiological function that correlates with such an enzymatic activity remained to be substantiated in LGG. To investigate the bacterial function, we constructed knock-out mutants in the corresponding genes aiming to establish a genotype to phenotype relation. Microscopic examination of the msp1 mutant showed the presence of rather long and overly extended cell chains, which suggests that normal daughter cell separation is hampered. Subsequent observation of the LGG wild-type cells by immunofluorescence microscopy revealed that the Msp1 protein accumulates at the septum of exponential-phase cells. The cell wall hydrolyzing activity of the Msp1 protein was confirmed by zymogram analysis. Subsequent analysis by RP-HPLC and mass spectrometry of the digestion products of LGG peptidoglycan (PG) by Msp1 indicated that the Msp1 protein has D-glutamyl-L-lysyl endopeptidase activity. Immunofluorescence microscopy and the failure to construct a knock-out mutant suggest an indispensable role for Msp2 in priming septum formation in LGG.